G355 To image or not to image? b cell non-hodgkins lymphoma (bnhl) and residual tissue on scan at disease reassessment in children under 12. (12th March 2018) - Green, K; Cheng, D
Abstract : Background/objectives: Children with BNHL have good outcomes with intensive upfront chemotherapy. Disease relapse or progression, whilst rare, is associated with very poor outcome hence the proven need for early disease assessment and escalation of chemotherapy if lacking a radiological early-treatment response. The value of post-treatment imaging surveillance or biopsy in children with residual imaging abnormalities in detecting and preventing disease relapse/progression is unclear. We evaluated whether our patients with BNHL with residual radiological abnormalities received follow-up imaging and biopsies, and how these investigations affected clinical outcomes. Design/methods: Data was collected for all children diagnosed with BNHL between 2006–2017 at a UK tertiary paediatric oncology centre. Measures included patient age at diagnosis, gender, histology, MYC status, and bone marrow or CNS involvement. Chemotherapy courses were recorded, including escalation of treatment from Group B to C. Follow-up imaging and clinic letters were analysed, with residual disease being categorised according to formal radiology reports. Results: 66 children aged 1 to 11 years were diagnosed with BNHL in the period studied; 57 males (86%) and 9 females (14%). 14 children had bone marrow positivity (21%), and 8 children CNS positivity (12%). 41 children (62%) had MYC positivity. At end of treatment, 28 children (42%) did have abnormal radiological findings; 4 of them underwent biopsy to exclude active disease. None of the children undergoing follow up imaging demonstrated disease relapse. Some children received multiple repeat scans involving either significant radiation exposure or general anaesthetic risk without altering outcomes.Overall survival was 94% (n=62), with 4 deaths. Of 4 deaths: 2 had good COP response on initial imaging but relapsed on treatment, 1 had stable residual disease on scans but died of secondary AML post BMT 1 did not respond to chemotherapy with clear progression of disease on imaging and palliation. Conclusions: Children with BNHL have good outcomes with intensive chemotherapy treatment. None of our patients with residual imaging abnormalities at treatment completion had disease relapse or progression, questioning the clinical need for longterm imaging, particularly if involving radiation. Biopsy provided reassurance without altering patient management. A protocol addition should be developed to guide follow up imaging where residual imaging abnormalities exist at end of treatment.